2022
DOI: 10.3390/gidisord4030011
|View full text |Cite
|
Sign up to set email alerts
|

Participation in Colorectal Cancer Screening among Migrants and Non-Migrants in Germany: Results of a Population Survey

Abstract: Colorectal cancer screening can contribute to reducing colorectal cancer incidence and mortality. Findings on disparities in the utilization of colorectal cancer screening between migrants and non-migrants have been inconsistent, with some studies reporting lower, and some higher utilization among migrants. The aim of the present study was to examine potential disparities in fecal occult blood testing and colonoscopy among migrants in Germany. Data from a population survey on 11,757 men and women aged ≥50 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Likewise, another study revealed that lack of CRC screening is related with lowsocioeconomic status. 30,31 The results showed that was no significant relationship between age and knowledge and attitude, respectively. Consistently, previous study reported similar results.…”
Section: Variablesmentioning
confidence: 89%
See 2 more Smart Citations
“…Likewise, another study revealed that lack of CRC screening is related with lowsocioeconomic status. 30,31 The results showed that was no significant relationship between age and knowledge and attitude, respectively. Consistently, previous study reported similar results.…”
Section: Variablesmentioning
confidence: 89%
“…The results showed that marital status was a predictive factor for attitude and female participants had better attitude. Likewise, another study revealed that lack of CRC screening is related with low‐socioeconomic status 30,31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with regard to a higher prevalence of several non-communicable diseases, such as cardiovascular diseases, type 2 diabetes mellitus, chronic pain, and certain psychological conditions [ 2 5 ]. The majority of studies on early cancer detection in Germany have further shown that migrants are less likely to use screening services for early detection of skin, cervical, and colon cancer [ 6 8 ], while participation rates for mammography screening were generally higher among women with a Turkish migration background and German resettlers from Eastern Europe [ 9 , 10 ]. Similarly, migrants are less likely to use hospice or palliative care services [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%